2007
DOI: 10.1177/070674370705200405
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Psychological Distress among SARS Survivors 1 Year after the Outbreak

Abstract: One year after the outbreak, SARS survivors still had elevated stress levels and worrying levels of psychological distress. The situation of health care worker SARS survivors is particularly worrying. The long-term psychological implications of infectious diseases should not be ignored. Mental health services could play an important role in rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

72
914
5
54

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,026 publications
(1,045 citation statements)
references
References 22 publications
72
914
5
54
Order By: Relevance
“…Embora tenham sido constatadas correlações significativas, porém fracas, na relação entre as versões da PSS e o QSG, os achados ratifi caram a convergência entre as escalas, tal como visto em pesquisas similares (Chaaya, Osman, Naassan, & Mahfoud, 2010;A. M. L. Lee et al, 2007;Örücü & Demir, 2009).…”
Section: Discussionunclassified
“…Embora tenham sido constatadas correlações significativas, porém fracas, na relação entre as versões da PSS e o QSG, os achados ratifi caram a convergência entre as escalas, tal como visto em pesquisas similares (Chaaya, Osman, Naassan, & Mahfoud, 2010;A. M. L. Lee et al, 2007;Örücü & Demir, 2009).…”
Section: Discussionunclassified
“…Although health care in contacts is focused mostly on early identification of somatic symptoms, concerns, anxiety, and stress experienced by those involved are also crucial. Guidelines should emphasize the need for individual support to assess and manage stress and to address questions about personal risks (29). …”
Section: Discussionmentioning
confidence: 99%
“…4 The 1-year follow-up study after the outbreak found that some SARS survivors had persistent mental problems. 4,5 Many studies found that the status of being a health care worker at the time of SARS infection, [5][6][7][8][9][10] the severity of the infection, and the dosage of steroid usage were related to the short-term mental outcomes. However, these studies were limited by the relatively modest sample sizes and the reliance on self-reported questionnaires.…”
mentioning
confidence: 99%